DESAIN KONSTRUKSI TAMBAHAN DAN ANALISA KEKUATAN MEMANJANG FLOATING DOCK 6000 TLC SEBAGAI AKSES PERBAIKAN KAPAL MENGGUNAKAN METODE FEM - rulianto, jangka; Arya Satria Wibawa; IGNA Satria Prasetya D. Y; Rochmad Eko Prasetyaning Utomo; Khairul Muzaka (Politeknik Negeri Banyuwangi, 2025)
Study This aim For designing construction addition and analysis strength elongated floating dock 6000 TLC as access repair boat use Finite Element Method (FEM). Problems found is ratio long a floating dock that doesn't sufficient when repair carried out on ships with 60 to 80 meters long, so worker difficulty working in parts tall bow and stern. For overcome problem this, design construction addition done with three variation long, that is 8 meters, 10 meters and 12 meters. Analysis results show that construction addition increase accessibility worker For repair ship on the part bow and stern. From third testing strength elongated show that construction addition capable withhold burden addition without exceed voltage permits set by American Bureau of Shipping (ABS). Voltage flexible maximum is 42.35 MPa for 8 meters variation, 59,741 MPa for 10 meters variation, and 71,486 MPa for 12 meters variation, meanwhile voltage shift maximum is 20,709 MPa for 8 meters variation, 29,038 MPa for variation of 10 meters, and 34.93 MPa for 12 meters variation. All variation own factor safety more big of 1, so structure stated safe For used. Keywords : ABS, Design, FEM, construction, stress